Antibacterial activity and mechanism of monolauroyl-galactosylglycerol against Bacillus cereus. (March 2018) - Diao, Mingming; Qi, Danping; Xu, Miaomiao; Lu, Zhaoxin; Lv, Fengxia; Bie, Xiaomei; Zhang, Chong; Zhao, Haizhen
Abstract: The antibacterial activity and mechanism of monolauroyl-galactosylglycerol (MLGG) against Bacillus cereus were investigated. The minimum inhibitory concentration of MLGG against B. cereus was 0.156 mg/ml. The inhibition growth curve assay also revealed that MLGG presented good antibacterial activity against B. cereus. Alkaline phosphatase activity assay, nucleotide leakage and cell viability analysis demonstrated that MLGG disrupted the integrity of cell wall and cell membrane of B. cereu s. Scanning electron microscopy and transmission electron microscopy results showed obvious morphological and ultrastructural changes of B. cereu s membrane, further confirming the damage of cell membrane integrity caused by MLGG. In summary, MLGG might exerted its antibacterial activity mainly by an action mode of membrane disruption, and it was expected to be an alternative for the development of new food preservatives. Highlights: It is the first time to report the antibacterial mechanism of glyceroglycolipids. Monolauroylgalactosylglycerol had strong antibacterial activity against Bacillus cereus. Monolauroylgalactosylglycerol exerted its antibacterial activity mainly by an action mode of membrane damage.